2013
DOI: 10.5194/hessd-10-2641-2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of stable water isotopes in alpine snow cover

Abstract: The aim of this study was to analyze and predict the mean stable water isotopic composition of the snow cover at specific geographic locations and altitudes. In addition, the dependence of the isotopic composition of the entire snow cover on altitude was analyzed. Snow in four Swiss catchments was sampled at the end of the accumulation period in April 2010 and a second time in Mai 2010 and analyzed for stable isotope composition of 2H and 18O. The sampling was conducted at both sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In theory, the isotopic composition of snow is significantly more depleted than other waters (Beria et al, 2018). However, melt processes and snow transformation can lead to an enrichment of the snowpack (Dietermann & Weiler, 2013). It has been shown that an enrichment of heavy isotopes in the upper snow layers takes place due to diffusion of water vapour in the pores of the snowpack and also partial melting, which causes evaporation and percolation of meltwater in the remaining snow (Gat, 1996; Stichler et al, 2001) as well as kinetic fractionation occurring during sublimation (Biederman et al, 2014; Gustafson, Brooks, Molotch, & Veatch, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In theory, the isotopic composition of snow is significantly more depleted than other waters (Beria et al, 2018). However, melt processes and snow transformation can lead to an enrichment of the snowpack (Dietermann & Weiler, 2013). It has been shown that an enrichment of heavy isotopes in the upper snow layers takes place due to diffusion of water vapour in the pores of the snowpack and also partial melting, which causes evaporation and percolation of meltwater in the remaining snow (Gat, 1996; Stichler et al, 2001) as well as kinetic fractionation occurring during sublimation (Biederman et al, 2014; Gustafson, Brooks, Molotch, & Veatch, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Here, the average isotope composition of precipitation shifts by 1.9‰/100/m for δ 2 H and 0.27‰100/m for δ 18 O, noting that in winter, above around 800 m asl, the precipitation is dominated by snow (Marty, ). Some version of this isotopic lapse rate is seen in almost all mountainous environments except on the leeward or “rain‐shadow” side of mountains, which receive precipitation from clouds that have already passed over the highest elevation of the ridge and are no longer continuing to rise, keeping the cloud condensation temperature relatively stable (Bershaw, Penny, & Garzione, ; Dietermann & Weiler, ; Koeniger, Hubbart, Link, & Marshall, ; Moran, Marshall, Evans, & Sinclair, ; Wen, Tian, Weng, Liu, & Zhao, ; Winograd et al, ). Moran et al () reported positive isotopic lapse rates (enrichment in heavier isotopes with increasing elevation) in snow samples on the leeward side of a glacierized valley in the Canadian Rockies (refer to Figure in Moran et al ()), which may occur only if the warmer temperatures and hence smaller vapor–liquid or vapor–ice isotopic fractionation factors offset the “rain‐out” effect.…”
Section: Background Of Isotope Hydrologymentioning
confidence: 99%
“…Snowmelt that leaves the snowpack preferentially discharges isotopically light water, thereby enriching the residual snowpack in heavier isotopes (Ala‐aho et al, ; Feng et al, ; Laudon, Hemond, Krouse, & Bishop, ; Shanley, Kendall, Albert, & Hardy, ; Soulsby, Malcolm, Helliwell, Ferrier, & Jenkins, ; Taylor et al, ; Taylor, Feng, Williams, & McNamara, ). It has been widely observed that early meltwater is more depleted in heavier isotopes and that, as the melt season progresses, both the residual snowpack and the generated meltwater become more enriched in heavier isotopes (Dietermann & Weiler, ; Taylor et al, ), which is also referred to as the melt‐out effect (Ala‐aho et al, ). To the best of our knowledge, the physical mechanisms of this melt‐out effect are not well understood but likely involve the partial melting of snowpack which results in preferential loss of lighter isotopes in the early season meltwater.…”
Section: Effects Of Snow Hydrologic Processes On the Isotopic Composition Of Watermentioning
confidence: 99%
“…Additional factors are melt‐related fractionation during the accumulation and/or the melting season, which is particularly affected by aspect, microtopography, vegetation, slope and (blowing) snow redistribution, isotopic fractionation between ice crystals and water within a snowpack during melt (Taylor, Feng, Williams, & McNamara, ), as well as differences in the time since the development of the snowpack or onset of melt (Table ). Fractionation due to sublimation leads to a strong enrichment of the topmost layers of the snowpack (Sokratov & Golubev, ; Dietermann & Weiler, ).…”
Section: Reported Spatial Variability In the Isotopic Compositionmentioning
confidence: 99%